Cytogenetic mapping of the W chromosome in the genus Leporinus (Teleostei, Anostomidae) using a highly repetitive DNA sequence - Marreta, M. E. [UNESP]; Faldoni, F. L. C. [UNESP]; Parise-Maltempi, Patricia Pasquali [UNESP] (Wiley-Blackwell, 2012)
The distribution of the Leporinus elongatus LeSpeI repetitive sequence in other Leporinus species was studied in an attempt to elucidate the evolutionary history of sex chromosomes in this genus using chromosome fluorescence in situ hybridization. The presence of fluorescent signals only in species that have differentiated sex chromosomes suggests that this sequence is related to the differentiation of sex chromosomes in this genus. Thus, these data will contribute to a better understanding of chromosome evolution, especially for sex chromosomes, in the Leporinus genus.
Keywords: chromosome evolution; FISH; sex chromosomes